Structural analysis of composite wind turbine blade using ANSYS. (2022) - Gukendran, R.; Sambathkumar, M.; Sabari, C.; Ranjith Raj, C.R.; Ranjeeth Kumar, V.
Abstract: Wind power is the most successful forerunners of technological breakthroughs that could result in more efficient energy output. Because of the rapid advancement in the energy sector, there is a growing need to increase the energy efficiency and lifetime of wind turbines. As a result, a detailed understanding of the activity of wind turbines under different load conditions is important. This paper investigates the performance of composite material of four different types. ANSYS Workbench is used to perform a detailed study of a typical wind turbine blade. The composite materials are tested for Total deformation, Equivalent Von-Mises stress, Maximum shear stress and strain energy and result values are noted.